1989
DOI: 10.23986/afsci.72347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different fertilization practices on the carotene content of carrot

Abstract: Abstract. The effects of different fertilization practices on the carotene content of carrot cv. Nantes Duke Notabene 370 Sv were studied in field experiments in southern Finland. Unirrigated and irrigated placement and broadcast fertilization, NPK fertirrigations without basic fertilization, NPK fertirrigations with NPK basic fertilization, and PK placement with N fertirrigations were compared. Further, single application was compared to split applications. Carotene determinations were done at harvest in 1985… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 4 publications
4
15
0
Order By: Relevance
“…In addition to chlorophyll, chloroplasts also contain carotenoids and proteins whose contents rise likewise in carrots with increasing use of nitrogen fertiliser. 25,38,39 An investigation by Habben 16 established a 138% increase of carotenoids in carrot leaves and a 10% increase in the roots through application of nitrogen fertiliser. Induction of chloroplast synthesis results from light energy and high nitrate content in the plant cell.…”
Section: 2233±35mentioning
confidence: 99%
“…In addition to chlorophyll, chloroplasts also contain carotenoids and proteins whose contents rise likewise in carrots with increasing use of nitrogen fertiliser. 25,38,39 An investigation by Habben 16 established a 138% increase of carotenoids in carrot leaves and a 10% increase in the roots through application of nitrogen fertiliser. Induction of chloroplast synthesis results from light energy and high nitrate content in the plant cell.…”
Section: 2233±35mentioning
confidence: 99%
“…Carotenoid synthesis is associated with the level of nitrogen in the soil, but the number of sunny days in the vegetation period is also a very important factor (Evers 1989). In the case of carrots, Kaack et al (2002) proved that when more mineral nitrogen was readily available in the soil at the beginning of the cultivation, more b-carotene was synthesized in carrot roots before the harvest time.…”
mentioning
confidence: 99%
“…On the other hand, Rembiałkowska (2000b) showed that two cultivars, Regulska and Montana, contained significantly more β-carotene when they were grown in the conventional system. Opposing this are reports by Evers (1989) and Rembiałkowska and Hallmann (2007), who found that the opposite was true, i.e. that organic carrots were richer in β-carotene.…”
Section: Resultsmentioning
confidence: 92%